BANKERS’ PERCEPTION ON THE DETERMINANTS OF CREDIT RISK IN CASE OF ETHIOPIAN COMMERCIAL BANKS - Sultan Jabir, Mohammed; Gizaw Tole, Million; Alemayehu Wolde, Haymanot (Journal of process management and new technologies, 2020)
This paper investigates the perception of bankers on the determinants of credit risk in Ethiopian commercial banks. Descriptive research design has been adopted in the study. In order to come across with the bankers perception, the study extensively used questionnaire. Bankers have been selected from 8 commercial banks operating in Ethiopia by using purposive sampling technique. The questionnaire was prepared to be filled by loan officers, relationship managers, credit analysts, credit directors and credit related position holders who work at each banks head office. The respondents were asked to give their perception regarding the determinants of credit risk by considering banks specific determinants, industry specific determinants and macro-economic determinants. Accordingly, based on the data generated the study found that from banks specific determinants poorly negotiated credit terms, compromised integrity in lending, poor credit risk assessment and higher rate of interest are the major causes for non-performing loans. Besides, from bank specific factors the study identified that the level of information sharing among banks has a direct impact on non-performing loans. The study also revealed that from macro-economic factors a rise in inflation rate, unemployment and foreign exchange rate decreases loan quality. The researchers suggests that to minimize credit risk the bank’s research and development department or the corporate planning division should perform a precise quantitative and qualitative analysis on determinants of Non-performing loans so as to act in a proactive and defensive ways.